2022
DOI: 10.3389/fnins.2022.894720
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resting-State Functional Connectivity of the Hippocampus in Rats With Sepsis-Associated Encephalopathy

Abstract: BackgroundSepsis-associated encephalopathy (SAE) has been identified as a frequent complication of sepsis, featured by an aberrant level of cognitive and affective functions. The present study is designed to explore the changes in functional connectivity (FC) of the hippocampus in rats with SAE utilizing resting-state functional magnetic resonance imaging (rs-fMRI).MethodsSprague-Dawley rats were randomly assigned to the SAE and control groups. We acquired rs-fMRI data using a 7T MRI to evaluate hippocampal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In our results, the increased ALFF values in the hippocampus supported the deteriorated behavioral results in the MWM test, which was consistent with a previous studies using the MWM test to evaluate hippocampal function (Barnhart et al, 2015). As shown in previous research, the brain functional connection between right hippocampus and thalamus increased in CLP induced SAE rats, and the enhanced functional values between the two regions were negatively correlated with behavioral performance in rats with SAE (Yao et al, 2022). These results suggested that CLP surgery not only increased regional spontaneous neuronal activity in hippocampus, but also enhanced the functional connection between hippocampus and other brain regions.…”
Section: Discussionsupporting
confidence: 92%
“…In our results, the increased ALFF values in the hippocampus supported the deteriorated behavioral results in the MWM test, which was consistent with a previous studies using the MWM test to evaluate hippocampal function (Barnhart et al, 2015). As shown in previous research, the brain functional connection between right hippocampus and thalamus increased in CLP induced SAE rats, and the enhanced functional values between the two regions were negatively correlated with behavioral performance in rats with SAE (Yao et al, 2022). These results suggested that CLP surgery not only increased regional spontaneous neuronal activity in hippocampus, but also enhanced the functional connection between hippocampus and other brain regions.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that hyperthyroidism affects the limbic system, which is crucial for memory consolidation and emotional regulation. The alterations may indicate cognitive or mental disorders associated with the hippocampus and other brain areas ( Li et al, 2017 ; Yao et al, 2022 ). Hyper-connectivity patterns may affect the functional connectivity of the default mode network, potentially impacting episodic memory and self-representation ( Zanão et al, 2017 ; Staffaroni et al, 2018 ; Ursino et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, disruptions in FC were observed in cerebellar-frontal circuits, with decreased connectivity between the left PLC and MTG within the attention network ( Li et al, 2017 ). Besides its motor coordination ability, the cerebellum increasingly recognized for its role in cognitive functions, including attention ( Li et al, 2017 ; Liu et al, 2017 ; Yao et al, 2022 ). Dysfunction within the cerebellum and frontal regions impairs the coordination and modulation of attention networks ( Arif et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Prior to this, Yao found that the functional connectivity (FC) changes between the hippocampus and other brain regions could serve as potential neuroimaging biomarkers for cognitive or mental disorders associated with Sepsis-associated encephalopathy (SAE). 9 In our prior investigation, we demonstrated the existence of disturbed FC in individuals with HM, particularly between the primary visual cortex (V1) and various other regions of the brain. This interference suggests that HM patients may be impaired in processing visual information.…”
Section: Introductionmentioning
confidence: 94%